Intra-Military Divisions and Democratization in South Korea. (October 2013) - Kim, Insoo
This paper investigates how a highly politicized system of military reshuffling under the authoritarian military regime contributed to the transition to democracy in South Korea in the 1980s. Through an analysis of individual data on 2, 666 Korean Military Academy (KMA) graduates, this study shows that promotion policies favored a small group of KMA graduates, called the Hana faction, who were preferentially treated in military promotions and recruited into the military leadership. These biased promotion procedures undermined the cohesion within the military as the marginalized non-Hana faction graduates became increasingly resistant to the subordination of their Hana faction superiors. This disintegration of military cohesion ultimately reduced the regime's capacity to block the transition to democracy.